2018
DOI: 10.18805/ijar.b-3447
|View full text |Cite
|
Sign up to set email alerts
|

Management of distal femoral diaphyseal fractures with string of pearls locking plate in dogs

Abstract: Distal femoral diaphyseal fractures in six dogs about 10-22 months old with body weight ranging from 12-25 kg were stabilized with String of Pearls (SOP) (Orthomed, UK) locking plates along with standard cortical and cancellous screws following standard AO/ASIF principles. Selection of appropriate size of plate and screws was according to body weight and type of fracture (2.7mm plate for dogs below 12 kg body weight and 3.5 mm plate for dogs above 12 kg body weight) which provided good fracture stability. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Usage of BIS in the evaluation of CNS depression with isoflurane, sevoflurane and propofol anesthesia in dogs was reported previously; however, research involving BIS in veterinary practice is limited (Greene et al, 2003;Belda et al, 2012;Saritas et al, 2013;Saritas et al, 2014a;Saritas et al, 2014b). It was determined that the effect of muscle relaxants on BIS values is limited in humans; however, no such studies have been conducted on dogs (Kumar et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Usage of BIS in the evaluation of CNS depression with isoflurane, sevoflurane and propofol anesthesia in dogs was reported previously; however, research involving BIS in veterinary practice is limited (Greene et al, 2003;Belda et al, 2012;Saritas et al, 2013;Saritas et al, 2014a;Saritas et al, 2014b). It was determined that the effect of muscle relaxants on BIS values is limited in humans; however, no such studies have been conducted on dogs (Kumar et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Complications related SOP plate as plate breakage (Kumar et al, 2018;Reddy et al, 2020;Fitzpatrick et al, 2012). Kim and Lewis (2014) reported that, the main disadvantage of using string of pearls bone plate was that the prominent profile of implants created soft tissue irritation.…”
Section: Complicationsmentioning
confidence: 99%